La evolución de la distribución normal (2015)
Statistics is the most widely applied of all mathematical disciplines and at the center of statistics lies the normal distribution, known to millions of people as the bell curve, or the bell-shaped curve. In this paper, the evolution of the most important probability distribution during several centuries is presented.